Structural health assessment of pavement sections in the southern central United States using FWD parameters - Bastola, Nitish R.; Souliman, Mena I.; Dessouky, Samer; Daoud, Raja (Frontiers in Built Environment, 2022)
Various Departments of Transportation (DOTs) in the South-Central States and elsewhere have made extensive use of the Non-Destructive Testing (NDT) surface deflection bowl data. The falling weight deflectometer (FWD) test is a popular NDT-based test used by transportation authorities to evaluate the performance of flexible pavement. Nevertheless, it is rare to develop a method for evaluating pavement sections using FWD data from all sensors. There is a constant demand for DOTs and highway agencies to have a streamlined approach that can be applied directly to their databases. This research focuses on extending and verifying the concept of previously published area ratio parameters to the pavement section of South-Central States (Arkansas, Louisiana, New Mexico, Oklahoma, and Texas) in order to properly analyze pavement performance. Simulation-based deflections are employed to strengthen deflection-based parameters and minimize the need for lengthy FWD field testing. Ninety-seven pavement sections in these states are being investigated for the implementation and validation of simplified processes that will be widely accessible to different transportation authorities in order to assess pavement problems at the network level.